KAPASITAS ORGANISASI INTERNASIONAL (PBB) DALAM MENENTUKAN SUATU ENTITAS (PALESTINA) SEBAGAI NEGARA - Wulandari, Ria (The Pontianak State Institute of Islamic Studies, 2015)
On December 2014 palestina to have member of International Criminal Court (ICC)it’s cause his status as a Observe Entity has change to become Observer State. A short time ago, in 2009, Palestina tried as member of ICC but not receivable cause his status.This article aims to explore about what are according international law an international organization have capacity to give state status for an entity. Finally, International Organization doesn’t have capacity for it although it’s universal international Organization.